Welding versus adhesive bonding strength investigation. (November 2021) - Seo, Junwon; Amatya, Ibin; Letcher, Todd; Jeong, Euiseok
Graphical abstract: Highlights: Tensile and shear strength tests were performed for adhesive and welded specimens. A database on the tested specimen strength was acquired through the tests. The effects of temperature and width on the strength were evaluated. The welded specimens had higher strength compared to the adhesive specimens. Metamodels and design equations were developed to replicate the measured strength. Abstract: This paper was intended to investigate the strength of adhesive and welded connections to be used in a dynamic message sign (DMS). The tensile strength and shear strength were studied for both of the adhesive and welded specimens. A number of tensile specimens and shear specimens with variations in width and temperature were tested until failure according to the ASTM D638 and ASTM D1002, respectively. The specimens with a range of width from 13 mm to 38 mm were conditioned with temperatures between −56.67 °C and 93.33 °C. The effects of temperature and width on each of the strengths were evaluated by analysing the testing data in a graphical and statistical manner. As expected, all the tests revealed that the welded specimens have significantly higher strength compared to the adhesive specimens in tensile and shear loadings. For the adhesive specimens, due to the increment of temperature, the highest increments were found to be 31.9% and 30.4%. In addition to the tests, Response Surface Metamodels (RSMs) and practical design equations were developed with regression analysis of the testing data, so as to predict tensile and shear stresses of both adhesive and welded specimens in an efficient way. 3D plots generated from the RSMs showed a higher effect of the temperature and width on the ultimate tensile and shear strength for both adhesive and welded specimens, and the practical design equations were founded to be more reliable for the overall tensile and shear stress prediction compared to the RSMs.